Vasoactive effects of stable aqueous suspensions of single walled carbon nanotubes in hamsters and mice. Issue 8 (December 2014) - Frame, Mary D; Dewar, Anthony M; Mullick Chowdhury, Sayan; Sitharaman, Balaji
Abstract Single-walled carbon nanotubes synthesized with iron (Fe-SWCNT) or gadolinium (Gd-SWCNT) show promise as high performance multimodal contrast and drug-delivery agents. Our purpose was to evaluate potential vasoactive effects of SWCNT. Stable aqueous solutions of Fe-SWCNTs or Gd-SWCNTs were made using the biocompatible amphiphilic polymer N-(carbonyl-methoxypolyethyleneglycol 2000)-1, 2-distearoylsn-glycero-3- phosphoethanolamine (PEG-DSPE). Both aggregated and non-aggregated (sonicated) formulations were tested. The initial vasoactivity of the formulations and their potential for inducing pro-inflammatory endothelial dysfunction were investigated in the hamster cheek pouch and murine cremaster muscle intravital microscopy models. These models provide an assay to test several formulations/dosages in a paired fashion. Abluminal exposure to small arterioles exposes both endothelial and vascular smooth muscle cells. Using abluminal exposures of dosages that would approximate the first pass of an i.v. bolus injection, both Fe-SWCNTs and Gd-SWCNTs were immediately vasoactive. Aggregated formulations induced dilation and non-aggregated formulations induced constriction in both hamsters and mice. Endothelial dysfunction was evident after exposure to either aggregated or non-aggregated forms. General loss of dilator capability was seen after exposure to non-aggregated but not aggregated forms. Thus concentrations mimicking bolus dosing of PEG-DSPE coated SWCNT induce both acute and chronic vascular responses.